Analysis of Divided Government Phenomena Post 2018 Governor Election in West Kalimantan - Andi Syarif T. U. W; Muh Ilham; Sampara Lukman; Ella Wargadinata (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze and find out and explain the symptoms of a divided government after the 2018 West Kalimantan governor election, the impact on government administration and the split government leadership model. The theoretical framework of this research is made in stages starting from the grand theory: Government Science and the Concept of Good Governance, middle-range theory: Conflict Theory, Cultural Concepts, Government Decentralization, Democratic Political System, Applied Theory: Leadership Theory (Nanus (1992: 136-141), Model Theory. This research uses qualitative methods, with data collection techniques through interviews, observations and documentation studies. The study results indicate that the direct election of the Governor and deputy governor of West Kalimantan Province will strengthen the decentralization system, which will have positive impacts; The first is the development of democratic life, including accountability to the people directly. Second, The legitimacy of the regional head from the people is getting higher. Namely, the principle of state sovereignty in the hands of the people is realized. Third, the support and participation of the people towards Government, development and social society are getting higher. However, it also has negative impacts, including, first, leaving a residue of conflict between supporters in the structure of society. Second, there is a pattern of a split government system that allows for disruption of government effectiveness. Third, implementation costs are not small, thus opening up opportunities for the Governor and Deputy Governor of West Kalimantan Province for corruption, collusion and nepotism. In the condition that the divided government pattern will minimize the negative impact on the wheels of Government which is less/ineffective, the Governor and Deputy Governor of West Kalimantan Province must build political support with the DPRD.